(untitled) (CIPEEX, 2024)
INTRODUCTION TRAUMA IN PREGNANT WOMEN IS THE MAIN NON-OBSTETRIC CAUSE OF MATERNAL MORBIDITY AND MORTALITY. THIS SYSTEMATIC REVIEW OF THE LITERATURE DISCUSSES TRAUMA, WHICH IS AN INJURY THAT INVOLVES ENERGY EXCHANGE BETWEEN THE ENVIRONMENT AND THE BODY AND THE ABDOMEN IS A REGION VULNERABLE TO TRAUMA, WHICH CAN COMPROMISE VITAL ORGANS. PREGNANT WOMEN ARE MORE LIKELY TO EXPERIENCE VIOLENT TRAUMA THAN NON-PREGNANT WOMEN. THUS, THE PROCESS OF SYSTEMATIZATION OF CARE FOR POLYTRAUMA PREGNANT WOMEN IS NECESSARY TO FACILITATE DECISION-MAKING, APPLYING THE ABCDE OF THE TRAUMA, ALWAYS ADEQUATELY MONITORING THE PREGNANT WOMAN. METHODOLOGY THIS IS A SYSTEMATIC LITERATURE REVIEW IN WHICH FIVE ARTICLES WERE ANALYZED IN THE PERIOD OF 2022 AND 2023. OBJECTIVE: TO ANALYZE THE RELEVANCE OF STUDIES ON POLYTRAUMA PREGNANT WOMEN. RESULTS: THE MAIN CAUSES OF TRAUMA IN PREGNANT WOMEN ARE: FALLS, DOMESTIC VIOLENCE, SEXUAL ABUSE AND TRAFFIC ACCIDENTS. HOWEVER, REGARDLESS OF THE CAUSE, CARE MUST BE AGILE AND EFFICIENT, WITH A FOCUS ON STABILIZING MATERNAL AND FETAL WELL-BEING. WHEN STARTING THE TREATMENT, IT IS NECESSARY TO PAY ATTENTION TO THE CHANGES OF THE PREGNANCY PERIOD, SUCH AS THE DISPLACEMENT OF THE INTESTINE TO THE UPPER ABDOMEN AND THE PRESENCE OF AMNIOTIC FLUID - WHICH CAN CAUSE EMBOLISM AND INTRAVASCULAR COAGULATION AFTER TRAUMA IN CASES OF INTRAVASCULAR SPACE GAIN. WHEN TRAUMA OCCURS, THESE STRUCTURES ABSORB PART OF THE ENERGY, BRINGING A FAVORABLE PROGNOSIS TO THE MOTHER AND AN EXTREMELY BAD PROGNOSIS TO THE FETUS. YOU SHOULD ALWAYS KEEP THE AIRWAY PERVEOUS, WITH ADEQUATE OXYGENATION AND VENTILATION. THUS, IT IS EXTREMELY IMPORTANT TO REFER TRAUMATIZED PREGNANT WOMEN, REGARDLESS OF THE DEGREE OF TRAUMA, TO A SERVICE WITH OBSTETRIC AND SURGICAL RESOURCES. IN RELATION TO THE FETUS, THE MAIN CAUSES OF DEATH ARE MATERNAL SHOCK, PLACENTAL DISPLACEMENT AND UTERINE RUPTURE. AFTER APPLYING ABCDE TO PREGNANT WOMEN, A FETAL ASSESSMENT IS NECESSARY, MONITORING FETAL HEARTBEATS AND PERFORMING CARDIOTOCOGRAPHY, IN ORDER TO ASSESS WHETHER THERE IS FETAL DISTRESS. CONCLUSION: IT IS CONCLUDED THAT WHEN COMPLICATIONS ARE NOT TREATED CORRECTLY AND AT THE CORRECT TIME, THE RISK OF DEATH AND/OR SEQUELAE FOR THE PREGNANT WOMAN INCREASES. IT IS IMPORTANT AND NECESSARY FOR THE TEAM THAT PROVIDES CARE TO CONSTANTLY TRAIN WITH THE AIM OF PROVIDING PREGNANT WOMEN WITH EXCELLENT CARE. THERE ARE FEW UPDATED NATIONAL ARTICLES ON TRAUMATIZED PREGNANT WOMEN, MAKING IT NECESSARY TO ENCOURAGE THE SEARCH AND FACILITATE THE PATIENT’S APPROACH TO UNDERSTANDING LOCAL EPIDEMIOLOGY AND DEVELOPING PREVENTION POLICIES. KEYWORDS: &NBSP;PREGNANCY; ADVANCED TRAUMA LIFE SUPPORT CARE; EMERGENCY CARE.